THE EFFECT OF WORK STRESSOR ON THE MIDWIFE PERFORMANCE IN RSKIA SADEWA YOGYAKARTA - Rahmadhani, Wulan; Maria Rosa, Elsye; Handari W, Sri (LPPM STIKES MUHAMMADIYAH GOMBONG, 2014)
Midwife is one resource that has an important role in the hospital. Midwife is very important because the job involves the safety of the mother and child during birthing. In performing its duties, midwife potentially experience of work stress are affected by the stressors of work consisting of the physical environment, individual, group and organizational. RSKIA Sadewa is one hospital that specialized in providing services for maternal and child health that attracted many people that have a lot of patients every month. A large number of patients who were not matched with adequate work environment will impact on job stress experienced by the midwives. The research was a descriptive analytic study. The populations of the study are all midwives working in Yogyakarta Sadewa RSKIA as many as 36 people. The sampling technique in this research is total sampling with amount of sample as many as 36 people. The data collect using questionnaires. Analysis data using multiple regression analysis. Physical environmental stressors have a significant effect on the performance of midwives. Individual stressors have a significant effect on the performance of midwives. Stressor groups significantly influence the performance of midwives. Organizational stressors have a significant effect on the performance of midwives.Work stressors consisting of the physical environment, individual, groups and organizations to simultaneously have a significant effect on the performance of midwives in RSKIA Sadewa Yogyakarta. Â Keywords: Job stressors, physical environment, midwifery performance